Clinical characteristics and correlation analysis of IVIG resistance in children with kawasaki disease complicated with hip synovitis: case-control study - Wang, Jianjie; Rong, Xing; Qiu, Huixian; He, Yue'e; Chu, Maoping; Wang, Zhenquan (Frontiers in Pediatrics, 2023)
Objective: To investigate the clinical characteristics and risk factors of Kawasaki disease (KD) complicated with hip synovitis. Methods: Children with KD admitted from January 1, 2011, to December 31, 2020, in the KD database of Yuying Children's Hospital Affiliated with Wenzhou Medical University were retrospectively included. We selected KD children with hip synovitis as the case group and KD children without hip synovitis as the control group to analyze the possible risk factors of hip synovitis in KD children.Results: Among 2871 KD children admitted to our center in recent years, 28 had hip synovitis.In this study 140 KD children were enrolled, including 28 KD children with hip synovitis and 112 children with general KD (within one month of admission). The onset age of KD patients with hip synovitis was 30.92 (23.23-49.99) months, and there were 17 cases of bilateral hip involvement. The course of synovitis (limited movement, joint pain, lameness, unwillingness to stand, etc.) ranged from 1 to 19 days, with an average of (8.8 ±4.6) days. We treated all KD children with IVIG (Intravenous immunoglobulin) plus aspirin, among which five patients in the case group developed coronary artery damage, six acquired IVIG resistance, and synovial inflammation disappeared within two weeks. Age, weight, length of stay, and incidence of IVIG resistance significantly differed between the two groups (P = 0.001, 0.005, < 0.001, and 0.035, respectively). Logistic regression analysis showed that KD combined with hip synovitis was an independent risk factor for developing propyl pellet resistance, with an OR value of 4.625 (95%CI: 1.095, 19.526).KD combined with hip synovitis mainly involves bilateral hip joints, and joint pain and limited movement are the main clinical features . The symptoms are mild and self-limiting. KD combined with hip synovitis is a risk factor for IVIG resistance. Hip synovitis is a good predictor of IVIG resistance.The etiology of Kawasaki disease (KD) is unknown, and it affects multiple systems throughout the body. These effects include coronary artery damage, pancreatitis, aseptic meningitis, synovitis, etc [1] .